Konark drashti - Mishra,Uday Narayan (Aman Parakashan, 2010)
MCQ Based on 1.Samskrutha kavya sasthra 2.Angresi kavya sasthra 3.Hindi kavya sasthra 4.Vyavaharik Sameeksha 5.Laghu Uththareeya athi laghu uththareeya prasna